JURNALISTIK DAKWAH (SEBUAH MODEL KOMUNIKASI ISLAMI) - Suf Kasman (Fakultas Dakwah dan Komunikasi, 2017)
One of the functions of journalism is as defenders of truth and fairness. Many people refer to it as a universal function and ideal. A journalist is never asked to provide information, but it is its own initiative. They offer an event that, in the presence of a reporter (messenger), will bridge the relationship between man, nature, and not the relationship between conqueror or conquered, or God's servant, but the relationship of togetherness in submission to Allah. Its existence is equivalent to the ministry, bureau, or other parts, which both have their own methods for achieving the goals of da’wah. The development dissemination of Islam tends to increase through electronic media, as well as print media. Journalism as a tool has a very powerful effect though it may appear slower, but leaves a deep impression.The existence of journalistic da’wah not only as a information tools of education and entertainment, but its main purpose is a religious leader as mission developing “Amar Ma’ruf Nahi Munkar”, in Al-Qur’an S. Ali Imran (3): 104.